A Study of Using the IoT-based Angklung Smart Band System to Support Music Group Activities for the Elderly in Nursing Homes - Nagul Cooharojananone; Pornprapit Phoasavadi; Saranya Hiranpanthaporn; Paphutsorn Wongratanapitak; Kanokwan Atchariyachanvanich (2022 Joint 12th International Conference on Soft Computing and Intelligent Systems and 23rd International Symposium on Advanced Intelligent Systems (SCIS&ISIS), 2022)
Angklung, the Indonesian musical instrument, has been used to promote the well-being of the elderly with music group activities. This leads to a shortage of hand sign angklung music experts in the city. This musical group activity is not widely utilized. The “Angklung Smart Band” is an IoT-based solution designed to assist angklung music experts or nursing home caregivers in Thailand in supporting angklung music group activities for the elderly. The system consists of a web application, Internet of Things devices, and angklung musical instruments linked through a wireless network. In this study, we evaluated the use of the angklung smart band to facilitate music group activities for the elderly in nursing homes. We compared the outcomes to the conventional hand sign method for promoting music group activities. We assessed the use of a smart band system with two groups of the elderly: a home group and a bedridden group. The results revealed that this approach is more appropriate for the home group than the bedridden group, since they can independently participate in music group activities. Consequently, the expert can focus on interaction with other elderly in order to ensure that all the elderly are always engaged in activities. A statistical analysis of the playing accuracy percentage showed that the smart band system can execute angklung music group activities as well as the hand sign method.
Keywords: Music Therapy and Health; Environmental Engineering and Cultural Studies; Technology Use by Older Adults